The Role of the Sharia Supervisory Board in Enhancing Sharia Compliance and Performance of Islamic Banks (A Case Study of Islamic Banks in West Java, Indonesia) - Indra Pramadita; Anisul Fata; Endang Pujiastuti (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2026)
The Sharia Supervisory Board (SSB) plays a crucial role in ensuring Sharia compliance and maintaining the integrity of Islamic banking operations. This study examines the role of the SSB in enhancing Sharia compliance and the financial performance of Islamic banks in West Java, Indonesia. Employing a case study approach with a mixed-methods design, this research utilizes primary data collected through questionnaires and semi-structured interviews with Sharia Supervisory Board members, bank management, and compliance officers, as well as secondary data obtained from audited annual reports. Quantitative analysis is conducted using multiple regression techniques, while qualitative data are analyzed thematically to capture governance practices and supervisory mechanisms. The results indicate that the effectiveness of the Sharia Supervisory Board—measured by expertise, independence, frequency of meetings, and level of involvement—has a significant positive impact on Sharia compliance and the financial performance of Islamic banks. These findings highlight the importance of strengthening Sharia governance structures to enhance both compliance and sustainability of Islamic banking institutions. This study contributes empirical evidence from a regional context and offers practical insights for policymakers and practitioners in improving Sharia governance frameworks.